PELATIHAN PENELITIAN TINDAKAN KELAS BAGI GURU UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DI KECAMATAN PASIR SAKTI - Devi Setyawati; Lia Lutfiana Dewi; Muhammad Maliki (RETEL Journal (Journal on Publication of The Research on Teaching and Language), 2016)
The Community Service Program (PPM) that is carried out aims to ensure that the training participants have the knowledge, ability and courage to conduct classroom action research, starting from making research proposals, conducting research and making research reports correctly, in accordance with research rules class actions commonly used in education. The implementation of the classroom action research is expected to improve the quality of learning at SD I Plus Ma'arif Nu 1 Al Firdaus. The design of the training was arranged so that the objectives were achieved effectively including the needs analysis activities compiled from devotees and schools, beginning with the submission of PTK training material by the PPM team, which was interspersed with questions and answers, assistance in making Class Action Research proposals, and presentation of the results of Class Action Research proposals by participants the training. The training method is carried out through lecture, group work and supervision methods. The results of the implementation of community service in general have been going well. The training was actively participated by 17 teachers who were divided into 5 groups. Each group prepares a CAR proposal with an agreed theme. The proposal preparation process is carried out properly through the mentoring process. At the end of the activity, each group presented the results of the PTK proposal and provided input by the PPM team. To achieve maximum results, it is expected that teachers of the Berbah National Vocational School should continue the results of the training at the implementation stage of Classroom Action Research so that teacher professional competency is achieved and the quality of learning is better